Extraction of cellulose nanofibers from cocos nucifera var aurantiaca peduncle by ball milling combined with chemical treatment. (15th May 2019) - Nagarajan, K.J.; Balaji, A.N.; Ramanujam, N.R.
Graphical abstract: Highlights: New Cellulose NanoFibers are extracted from Cocos nucifera var-Aurantiaca peduncle. TGA analysis shows that CNFs are thermally stable until 230 °C. TEM shows that CNFs appears web-like structure with the range of 55–64 nm width. Characterized CNFs has the potentiality to replace the artificial nano particles. Abstract: The development of bio-degradable, renewable and low-cost material is critical to meet the growing environmental concerns and energy demands. The present study emphasizes on the extraction of a new kind of Cellulose NanoFibers (CNFs) from peduncles which are a bio-waste product of Cocos nucifera var-Aurantiaca through ball milling combined with chemical treatment. The crystallinity index, presence of functional groups and elemental composition in CNFs were identified by employing XRD, FT-IR and EDX techniques. The thermal stability of CNFs was investigated by thermo-gravimetric analysis. The morphological analysis was performed by electron microscopy and the results showed the appearance of CNFs in web-like structure with a width of 55–64 nm. The effect of reinforcement of CNFs in epoxy matrix was performed, whose tensile strength increased by 37% when 2 wt% of CNFs was loaded into the matrix.